Fibronectin-Expressing Mesenchymal Tumor Cells Promote Breast Cancer Metastasis - Jun, Brian H. (Cancers (Basel), 2020)
SIMPLE SUMMARY: For cancer to metastasize, tumor cells must not only invade the local tissue but must also grow and proliferate once they arrive. Tumor cell heterogeneity, the presence of multiple types of cancer cells within a tumor, can increase cell proliferation and invasion through cooperative interactions, increasing the potential for metastasis. We recently found that pro-invasion cancer cells express the protein fibronectin and increase metastasis for pro-growth cancer cells. We investigated this interaction by analyzing these two cell types’ migration and survival, both alone and in co-cultures. We find that pro-invasion cells have a protective effect on pro-growth cells, which otherwise die after two days in nutrient-starved conditions. Further, we find that adding soluble fibronectin to pro-growth cells in culture was sufficient to improve survival. However, their survival was higher for co-culturing conditions. These studies highlight the importance of cancer cell heterogeneity and the role of fibronectin in metastasis. ABSTRACT: Tumor metastasis is connected to epithelial-mesenchymal heterogeneity (EMH) and the extracellular matrix (ECM) within the tumor microenvironment. Mesenchymal-like fibronectin (FN) expressing tumor cells enhance metastasis within tumors that have EMH. However, the secondary tumors are primarily composed of the FN null population. Interestingly, during tumor cell dissemination, the invasive front has more mesenchymal-like characteristics, although the outgrowths of metastatic colonies consist of a more epithelial-like population of cells. We hypothesize that soluble FN provided by mesenchymal-like tumor cells plays a role in supporting the survival of the more epithelial-like tumor cells within the metastatic niche in a paracrine manner. Furthermore, due to a lower rate of proliferation, the mesenchymal-like tumor cells become a minority population within the metastatic niche. In this study, we utilized a multi-parametric cell-tracking algorithm and immunoblotting to evaluate the effect of EMH on the growth and invasion of an isogenic cell series within a 3D collagen network using a microfluidic platform. Using the MCF10A progression series, we demonstrated that co-culture with FN-expressing MCF10CA1h cells significantly enhanced the survival of the more epithelial MCF10CA1a cells, with a two-fold increase in the population after 5 days in co-culture, whereas the population of the MCF10CA1a cells began to decrease after 2.5 days when cultured alone (p < 0.001). However, co-culture did not significantly alter the rate of proliferation for the more mesenchymal MCF10CA1h cells. Epithelial tumor cells not only showed prolonged survival, but migrated significantly longer distances (350 µm compared with 150 µm, respectively, p < 0.01) and with greater velocity magnitude (4.5 µm/h compared with 2.1 µm/h, respectively, p < 0.001) under co-culture conditions and in response to exogenously administered FN. Genetic depletion of FN from the MCF10CA1h cells resulted in a loss of survival and migration capacity of the epithelial and mesenchymal populations. These data suggest that mesenchymal tumor cells may function to support the survival and outgrowth of more epithelial tumor cells within the metastatic niche and that inhibition of FN production may provide a valuable target for treating metastatic disease.